Introducing Coffee as a Complementary Agent Beside Metformin Against Type 2 Diabetes - Majid Rezaei Tavirani; Masoumeh Farahani; Mostafa Rezaei Tavirani*; Zahra Razzaghi; Babak Arjmand; Mahmood Khodadoost (Iranian Society of Pharmacognosy, 2024)
Background and objectives: Positive role of coffee consumption on regulation of human blood sugar has been highlighted by researchers. On the other hand, metformin is the common drug against type 2 diabetes. This study aimed to explore possible ways to use coffee as a complementary agent beside metformin or independently versus type 2 diabetes. Methods: Proteomic data about effect of two major compounds of coffee (caffeine and trigonelline) on improvement of diabetic condition was searched and analyzed via protein-protein interaction (PPI) network analysis and gene ontology enrichment. Gene expression profiles of human whole blood of diabetic patients (responsive to metformin) versus control were extracted from GSE83983 which is recorded in Gene Expression Omnibus (GEO) database. After pre-evaluation of data by GEO2R program, the significant differentially expressed genes (DEGs) were assessed via PPI network analysis and regulatory network evaluation. Results: Caffeine and trigonelline effectively regulate the glycolytic processes to fight against diabetic condition. HSP90AA1, TLR4, RELA, ARRB, LRRK2, STAT5B, LYN, and TLR2 genes that are involved in diabetes were affected significantly by metformin. Conclusion: It can be concluded that coffee consumption can improve sugar regulation in diabetes similar to metformin. IT seems that the optimized consumption quantity of coffee can be considered as controller of blood sugar in diabetic patients.